Resource allocation for multi-conductor power-cable carrier communications systems - XU Zhi-qiang1; ZHAI Ming-yue1; ZHAO Yu-ming2 (Tongxin xuebao)
Based on the measurements of cross-interfere coupling coefficient in a multi-conductor power cable, the characteristics of signal cross-interfere were analyzed. The mixed resource allocation model based on power-rate adaptation was introduced with the restrictions of power-line communications. Owing to the limitation of lagrange multiplier method used to solve the resource allocation problem with cross-interfere, linear transformation was applying for the transmitting signal and its correlative parameters to decouple channels’ cross-interfere and decompose the complicated allocation problem into multiple simple equivalent channel optimization problems. A novel bit adding/subtracting algorithm based on SVD-GMD decoupling and dirty-paper coding was proposed with the classical water-filling theory, and another bit adding look-up table algorithm based on SVD decoupling is also proposed for comparison. In the typical multi-conductor power-cable environment, the simulation results indicate the bit adding/subtracting algorithm can eliminate the cross-interfere between equivalent channels and utilize the comparability of equivalent channels effectively, and keep the optimal system performances with the lower complexity.